2011
DOI: 10.1007/s00441-011-1181-y
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 → SMAD/p53/USF2 → PAI-1 transcriptional axis in ureteral obstruction-induced renal fibrosis

Abstract: Chronic kidney disease constitutes an increasing medical burden affecting 26 million people in the United States alone. Diabetes, hypertension, ischemia, acute injury, and urological obstruction contribute to renal fibrosis, a common pathological hallmark of chronic kidney disease. Regardless of etiology, elevated TGF-β1 levels are causatively linked to the activation of profibrotic signaling pathways initiated by angiotensin, glucose, and oxidative stress. Unilateral ureteral obstruction (UUO) is a useful and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
140
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(147 citation statements)
references
References 158 publications
1
140
2
Order By: Relevance
“…On the other hand, wild‐type p53 could repair the cells even with genetic abnormalities31 and might cause drug resistance to temozolomide 32. SERPINE1 was generally considered as the downstream gene of p53 and could be induced by the activation of p53 33, 34. However, our study found that the up‐regulation of SERPINE1 repressed p53 signalling pathway, whereas miR‐1275 had an inverse effect, which has not been reported in previous studies.…”
Section: Discussioncontrasting
confidence: 87%
“…On the other hand, wild‐type p53 could repair the cells even with genetic abnormalities31 and might cause drug resistance to temozolomide 32. SERPINE1 was generally considered as the downstream gene of p53 and could be induced by the activation of p53 33, 34. However, our study found that the up‐regulation of SERPINE1 repressed p53 signalling pathway, whereas miR‐1275 had an inverse effect, which has not been reported in previous studies.…”
Section: Discussioncontrasting
confidence: 87%
“…TGF-β 1 is a common profibrotic factor that mediates the pathologic process of fibrosis in multiple organs (Matsuoka and Tsukamoto 1990;Wen et al 2010;Lang et al 2011;Samarakoon et al 2012). Matsuoka and Tsukamoto (1990) found that TGF-β 1 plays critical role in pathogenetic role in alcoholic liver fibrogenesis by stimulation of hepatic lipocyte collagen production.…”
Section: Discussionmentioning
confidence: 99%
“…However the intermediate molecule and signaling pathway are unknown. Realizing that TGF-β 1 is a common profibrotic factor which mediates the pathologic process of fibrosis in multiple organs (Matsuoka and Tsukamoto 1990;Wen et al 2010;Lang et al 2011;Samarakoon et al 2012), we hypothesize that TGF-β 1 is responsible for androgen deprivation-induced fibrosis in bladder tissues. To test this hypothesis, firstly we measured the TGF-β 1 mRNA levels Androgen deprivation induced TGF-β production contributes to induction of pro-collagen I mRNA expression level.…”
Section: Tgf-β Is a Signaling Molecule Responsible For Androgen Deprimentioning
confidence: 98%
“…One confounding variable is the correctness of the UUO model in terms of the primary role of myofibroblasts and TGF-β1. A recent review supports the interpretation of Park et al [6] and other observers [8]. However, what if this view is oversimplified or not correct?…”
mentioning
confidence: 85%